PRACTICAL PRINCIPLES OF SOCIAL SPHERE EXPERTS PREPARATION FOR SOCIAL AND PEDAGOGICAL SUPPORT OF MATERNITY AND CHILDHOOD IN UKRAINE - Stynska, Viktoriia (Mountain School of Ukrainian Carpaty, 2022)
The article is devoted to the specifics of practical preparation of social sphere experts for socio-pedagogical support of motherhood and childhood in Ukraine. Analysis of theoretical and practical foundations of socio-pedagogical support of motherhood and childhood in Ukraine in the 20th century proved the readiness research need of future social workers/social pedagogues for socio-pedagogical support of motherhood and childhood in Ukraine. We consider this readiness as the desire of a social worker/social pedagogue to implement social services at the macro, meso, and micro levels, as well as personal motivation and professional growth (improvement of professionally oriented knowledge and skills) in the field of socio-pedagogical support of motherhood and childhood. The article presents the characteristics of criteria, indicators of readiness of social workers/social pedagogies choice «Social-pedagogical support of motherhood and childhood: theory and practice», on the basis of which the criteria for evaluating the effectiveness of social workers/social pedagogues preparation for social-pedagogical support of motherhood and childhood in Ukraine were characterized (motivational, substantive , operational), adapted to study the phenomenon under study. On the basis of selected criteria and indicators, three levels of social workers/social pedagogues readiness for socio-pedagogical support of motherhood and childhood in Ukraine are distinguished (high, medium, low). The results of the verification of the feasibility of using the author’s course in the preparation of future social workers/ social pedagogues for socio-pedagogical support of motherhood and childhood in Ukraine showed that at the final stage, the averaged quantitative indicators of a high level according to three criteria increased in EG to 26.92% (against 12, 73% at the beginning of the research) and in CG - up to 13.32% (against 12.81% at the beginning of the research); average - up to 53.74% (against 39.11% at the beginning of the research) in EG and up to 39.54% (against 38.95% at the beginning of the research) in CG. Low-level indicators in EG are 19.34% (versus 48.16% at the beginning of the research) and 47.13% (versus 48.25% at the beginning of the research) in CG. The processing of the obtained results confirmed the statistical positive dynamics. It was concluded that developed and implemented author's course has practical significance and prospects of feasibility of use in the practical preparation of future social workers/social pedagogues for socio-pedagogical support of motherhood and childhood in Ukraine. Keywords: preparation, readiness, socio-pedagogical support, motherhood, childhood, social worker, social pedagogue, social sphere experts.